The Effects of Cannabidiol on the Driving Performance of Healthy Adults: A Pilot RCT - Toni Marie Rudisill, MS, PhD; Karen (Kim); Sijin Wen, PhD; Treah Haggerty, MD; Gordon S. Smith, MB ChB (Elsevier, 2023)
Introduction: A common side effect of cannabidiol is drowsiness, which could impact safe driving. This study's purpose was to determine the feasibility and whether cannabidiol impacts simulated driving performance. Methods: This was a randomized, parallel-group, sex-stratified, double-blind, pilot trial that consisted of a volunteer sample of healthy, currently driving college students. Participants were randomized and allocated to receive a placebo (n=19) or 300 mg cannabidiol (n=21) by oral syringe. Participants completed a ∼40-minute driving simulation. A post-test survey assessed acceptability. The primary outcomes were mean SD of lateral position, total percent time the individual drove outside travel lanes, total collisions, time to initial collision, and mean brake reaction time. Outcomes were compared between groups using Student's t-tests and Cox proportional hazards models. Results: None of the relationships were statistically significant, but the study was underpowered. Those receiving cannabidiol experienced slightly more collisions (0.90 vs 0.68, p=0.57) and had slightly higher mean SD of lateral position and slower brake reaction times (0.60 vs 0.58 seconds, p=0.61) than those who received placebo. Participants were satisfied with their experiences. Conclusions: The design was feasible. Larger trials may be warranted because it is unclear whether the small differences in performance seen in the cannabidiol group were clinically relevant.